Genomic Analysis of Terpene Synthase Family and Functional Characterization of Seven Sesquiterpene Synthases from Citrus sinensis - Alquézar, Berta; Rodríguez, Ana; de la Peña, Marcos; Peña, Leandro (Frontiers in Plant Science, 2017)
Citrus aroma and flavor, chief traits of fruit quality, are derived from their high content in essential oils of most plant tissues, including leaves, stems, flowers, and fruits. Accumulated in secretory cavities, most components of these oils are volatile terpenes. They contribute to defense against herbivores and pathogens, and perhaps also protect tissues against abiotic stress. In spite of their importance, our understanding of the physiological, biochemical, and genetic regulation of citrus terpene volatiles is still limited. The availability of the sweet orange (Citrus sinensis L. Osbeck) genome sequence allowed us to characterize for the first time the terpene synthase (TPS) family in a citrus type. CsTPS is one of the largest angiosperm TPS families characterized so far, formed by 95 loci from which just 55 encode for putative functional TPSs. All TPS angiosperm families, TPS-a, TPS-b, TPS-c, TPS-e/f, and TPS-g were represented in the sweet orange genome, with 28, 18, 2, 2, and 5 putative full length genes each. Additionally, sweet orange β-farnesene synthase, (Z)-β-cubebene/α-copaene synthase, two β-caryophyllene synthases, and three multiproduct enzymes yielding β-cadinene/α-copaene, β-elemene, and β-cadinene/ledene/allo-aromandendrene as major products were identified, and functionally characterized via in vivo recombinant Escherichia coli assays.